GAMBARAN DUKUNGAN SOSIAL KELUARGA PADA LANSIA DALAM MENGIKUTI KEGIATAN DI POSYANDU LANSIA - Khosasih, Ikhwan; Saputri, Leviana (Jurnal AKP, 2014)
Advanced age (elderly) are people over 60 years old wich generallyÂ  experiencing phisyical changes a disturbance. Those changes include physical, mental, social, and psychological. Canges monitor the issues and the changes, the elderly are expected to follow the activities in Elderly - integrated service post. One of the factors causing the elderly participation in the Ederly â intergrated sevice post is theÂ  support of the families.The objective of this study is to describe family support to the elderly in following activities in Elderly â integrated service post . The design used in this study was descriptive. Its population is the entire family that has older age amount of 69 respondents. Technique sampling was Total sampling. The variable of this study was family support of the elderly. Data collectied by using questionnaires, while the data processing was descriptive data analysis.The results revealed that most respondents have family support in sufficient criteria were 30 respondents (43%), sufficient criteria there 24 respondents (35%) is less and 15 respondents (22%) isÂ  good criteria.From the results of this study concluded that most of the respondents have sufficient family support. And need to improve tha family support by counseling and information to families about the importance of Ederly â integrated services post. Keywords: Elderly, Family Social Support.